2014
DOI: 10.4236/am.2014.511163
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Grouping Healthy Subjects’ Sensitivity to Pain and Its Relationship to Personality Traits: Results of a Cluster Analysis

Abstract: Objective: Individual differences in the sensitivity to pain and the factors that may contribute to these differences are well studied. Nevertheless, there is no single test that can reliably classify subjects as being sensitive or insensitive to pain. Methods: In the present study, hierarchical clustering and K-means cluster analysis was used to identify subgroups among 191 healthy subjects (105 females, 86 males) according to their sensitivity to pain. Group determination was based on the subjects' response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…It seems that Openness-to-Experience could serve as the opposite anchor of harm avoidance. Notably, while Pud et al (2014) tested the relation between pain sensitivity and personality dimensions in the lab, our findings not only support their results, but have the additional advantage of being able to be extrapolated to environments outside the lab.…”
Section: Personality Traits and Pain Perceptionsupporting
confidence: 78%
See 3 more Smart Citations
“…It seems that Openness-to-Experience could serve as the opposite anchor of harm avoidance. Notably, while Pud et al (2014) tested the relation between pain sensitivity and personality dimensions in the lab, our findings not only support their results, but have the additional advantage of being able to be extrapolated to environments outside the lab.…”
Section: Personality Traits and Pain Perceptionsupporting
confidence: 78%
“…In the present study, Neuroticism was found to have the strongest correlations (among all five personality traits) to all three daily pain sensitivity measures. While Neuroticism is characterized by tenseness, moodiness, and anxiety (Martínez et al, 2011;Littman-Ovadia and Lavy, 2012), it is the trait most similar to harm avoidance (Pud et al, 2014). Openness-to-Experience, which this study found negatively correlated to daily pain sensitivity, denotes having wide interests and being imaginative and insightful (Littman-Ovadia and Lavy, 2012).…”
Section: Personality Traits and Pain Perceptionmentioning
confidence: 67%
See 2 more Smart Citations
“…4,10,11,21,23,29,3335,45,53,60,68,69,72 Among these, the Multidimensional Pain Inventory 33 (MPI) is probably the best known. The MPI emerged from biopsychosocial theory, and studies assessing outcomes based on MPI classification indicate that anatomically distinct disorders (headache, TMD, back pain) respond to treatments similarly within each cluster.…”
Section: Discussionmentioning
confidence: 99%